The Relationship between Child Hospitalization Duration and Parent Anxiety Level at Rs Tiara Sella Bengkulu City 2023 - Ulyah, Qomariyatul; Murwati, Murwati; Rossita, Taufianie (Universitas Dehasen Bengkulu, 2024)
Children who are hospitalized will affect their physical and psychological state, this matter is called hospitalization (Apriany, 2018). Parents when children undergo hospitalization often experience anxiety due to stress. The problem of anxiety in parents if they do not have a good coping mechanism, can become severe anxiety or panic.Research Objectives The relationship between the length of hospitalization of children and the level of anxiety of parents at Tiara Sella Hospital Bengkulu Year 2023.This type of research is analytical research using a cross-sectional design which is a research design by measuring or observing at the same time (once in a while) between risk factors / exposure and disease (Hidayat, 2020). The population of this study was The population of this study were parents whose children underwent hospitalization totaling 120 people. the number of samples in this study was 55.The results of this study indicate that more than half of the respondents 30 (54.5%) stated that the length of stay was ≤ 5 days at Tiara Sella Hospital, Bengkulu City, 2023, Half of the respondents 28 (50.9%) stated mild anxiety at Tiara Sella Hospital, Bengkulu City, 2023, There is a relationship between the length of hospitalization of children and the level of anxiety of parents at Tiara Sella Hospital, Bengkulu City, 2023. The results of this study suggest that the Tiara Sella Hospital should pay more attention to the health status of children, not only physical problems but also their psychological adaptation in undergoing hospitalization in the hospital. The role of the hospital can be improved in one way such as: providing counseling for parents.